Acute neuroborreliosis presenting with severe hyponatremia: a case report - Ismaïl Ould-Nana; Pierre-Yves Decleire; Sabina Boangher; Philippe Glorieux (Greater Baltimore Medical Center, 2021)
A 79-year-old Caucasian woman was admitted to the hospital with a 1-week history of general deterioration, describing malaise, abdominal pain, vomiting and diarrhea. Concomitantly, she presented with urinary retention. Laboratory tests revealed severe hyponatremia secondary to the syndrome of inappropriate antidiuretic hormone secretion (SIADH). Patient reported a tick bite 1 month earlier, followed by erythema migrans. The diagnosis of Lyme disease was immediately suspected and confirmed by positive IgM and IgG serology. Symptoms and electrolyte disturbances completely resolved with a 2-week course of doxycycline. This case highlights the need to consider osis as a cause of hyponatremia and SIADH in an endemic region.